Banker to the poor : micro-lending and the battle against world poverty - Yunus, Muhammad, 1940- (PublicAffairs, 2007)
Winner of the 2006 Nobel Peace Prize. This autobiography of the world-renowned, visionary economist who came up with a simple but revolutionary solution to end world poverty--micro-credit--has become the classic text for a growing movement.